GBHN DAN PERUBAHAN PERENCANAAN PEMBANGUNAN DI INDONESIA GBHN - Subkhan, Imam (Jurnal Aspirasi, 2014)
After more than a decade Indonesia entered the Reform era, there is now a desire among some politicians and intellectuals to revive the concept of the Guidelines (GBHN) to guide development planning as it was once used under the New Order regime. The desire was based on the view that the current development planning has led to much turmoil, collision and no sustainability. This paper describes the Guidelines used for development planning in the reform era called Long Term Development Plan (RPJPN) is somewhat similar to the Guidelines (GBHN) in the perspective of theory of modernization development. Therefore, chaos, development planning collision is actually not caused by the absence of the Guidelines itself, but rather on the changes of the state power system into more horizontal system so that no state agency is able to fully control the development planning from the center down to regions, something which was done well in the era of the New Order.